1989
DOI: 10.1523/jneurosci.09-09-03306.1989
|View full text |Cite
|
Sign up to set email alerts
|

Vision calibrates sound localization in developing barn owls

Abstract: This study demonstrates that continuous exposure of baby barn owls to a displaced visual field causes a shift in sound localization in the direction of the visual displacement. This implies an innate dominance of vision over audition in the development and maintenance of sound localization. Twelve owls were raised from the first day of eye opening wearing binocular prisms that displaced the visual field to the right by 11 degrees, 23 degrees, or 34 degrees. The prisms were worn for periods of up to 7 months. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 17 publications
5
83
2
Order By: Relevance
“…This is consistent with their life history, as they hide in root systems, grasses and debris during daylight hours when visual cues are present Stamper et al, 2010). Similarly, other nocturnal or crepuscular animals that can rely on non-visual sensory information for the control of behavior also preferentially rely on visual cues when they are present (Knudsen and Knudsen, 1989;Penteriani et al, 2007;Cummings et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…This is consistent with their life history, as they hide in root systems, grasses and debris during daylight hours when visual cues are present Stamper et al, 2010). Similarly, other nocturnal or crepuscular animals that can rely on non-visual sensory information for the control of behavior also preferentially rely on visual cues when they are present (Knudsen and Knudsen, 1989;Penteriani et al, 2007;Cummings et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…King et al 1988;Knudsen and Knudsen 1989;Knudsen and Knudsen 1990;Brainard and Knudsen 1998;Knudsen 2002). Largely because of the convenience of a topographical representation of auditory space, much of this work has exploited the superior colliculus of the mammal or the barn owl.…”
Section: Recalibration To Modified Spectral Cuesmentioning
confidence: 99%
“…Moreover, juvenile owls frequently exhibited full map shifts without hunting and while housed in small individual cages (Knudsen and Knudsen, 1989b). Thus the high degree of plasticity expressed in hunting adult owls is still less than the plasticity expressed by juvenile owls during the sensitive period.…”
Section: Developmental Regulation Of Plasticitymentioning
confidence: 99%
“…Recent studies have shown that environmental factors such as social interactions and environmental richness also modulate plasticity (Newport et al, 2001;Goldstein et al, 2003;Cancedda et al, 2004). Barn owls pass through a similar sensitive period during which experience exerts an exceptionally strong shaping influence on sound localization behavior (Knudsen and Knudsen, 1989b). The effects of experience on sound localization have been traced to specific sites within the owl's midbrain, making it possible to correlate behavioral learning with changes in underlying neural circuits (Feldman and Knudsen, 1998;DeBello et al, 2001).…”
Section: Introductionmentioning
confidence: 99%